2023
DOI: 10.1111/gcb.16826
|View full text |Cite
|
Sign up to set email alerts
|

Declining tree growth resilience mediates subsequent forest mortality in theUSMountain West

Abstract: Rising global temperatures due to human greenhouse gas emissions pose a threat to Earth's forests. Notably, increasing temperature has been linked to higher frequency and intensity of drought-induced forest background mortality and die-off (Allen et al., 2015;Breshears et al., 2009;Williams et al., 2012). Largescale forest die-off is of particular concern due to its dramatic disruption of forest function, with large consequences on biodiversity (Betts et al., 2017;Feng et al., 2021), ecosystem goods and servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 99 publications
(173 reference statements)
0
4
0
Order By: Relevance
“…Yet they can be performed for many species, facilitated by efforts to aggregate species occurrence records like the Global Biodiversity Information Facility (GBIF, Robertson et al., 2014). Additionally, our findings point to the utility of considering not just a single study site when analyzing a particular species, but studying the same species' behavior across an expansive network of study sites (e.g., Cabon et al., 2023; Lockwood et al., 2023; Novick, Jo, et al., 2022), so that the roles of climate, soil, and topography are at least partially integrated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Yet they can be performed for many species, facilitated by efforts to aggregate species occurrence records like the Global Biodiversity Information Facility (GBIF, Robertson et al., 2014). Additionally, our findings point to the utility of considering not just a single study site when analyzing a particular species, but studying the same species' behavior across an expansive network of study sites (e.g., Cabon et al., 2023; Lockwood et al., 2023; Novick, Jo, et al., 2022), so that the roles of climate, soil, and topography are at least partially integrated.…”
Section: Discussionmentioning
confidence: 84%
“…Because plant hydraulic traits vary significantly by species (Bartlett et al., 2016; Skelton et al., 2015), many studies of plant drought and water stress response analyze vegetation behavior as a function of species (e.g., Brzostek et al., 2014; Cabon et al., 2023; Serra‐Maluquer et al., 2022). However, the focus on species‐by‐species differences in studies of plant water stress neglects the fact that plant hydraulic traits may exhibit significant intra‐specific variability (González de Andrés et al., 2021; Kannenberg et al., 2022; Lu et al., 2022), including through adaptation to local climate (Depardieu et al., 2020; Pritzkow et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that long-term rises in instability and reduced growth predispose European beech to elevated mortality risks under future climate-induced stress conditions (Gillner et al ., 2013; DeSoto et al ., 2020; Cabon et al ., 2023). The loss of stability in our study sites emphasizes the need for continuous monitoring and proactive management of beech forests, particularly in regions where climate change is projected to increase the frequency and severity of droughts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our analysis of EWS reveals the loss of resilience after an extreme event, as notably observed at the TRE site. In the context of climate model projection, the increase in the frequency and severity of droughts, the ability to detect earlier tipping points of critical slowdowns in declining systems, and the potential for recovery to the current state or an alternative state remains uncertain (Cabon et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%